Peningkatan Prestasi Belajar Membaca dan Menulis Melalui Penggunaan Alat Peraga pada Siswa Kelas 1 SDI Wolowona 1 - Adelfrida Kemba (Program Studi Pendidikan Ekonomi, Universitas Flores, 2019)
Improving the quality of basic education, especially in elementary schools, has become a government policy, which must be implemented and realized as well as possible. This effort is carried out in order to improve the quality of human resources.One of the main emphases in the purpose of basic education is that primary school graduates master